Developing an Educational Unit in Biology based on Visual Learning and its Effect in Enhancing Scientific Images Reading Skills for Ninths Grade Students - O. Alaeesa, Mohammad; R. Malkawi, Aamal (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to develop an educational unit in the light of visual learning and to know its effect on improving the skills of reading scientific images among the ninth-grade students in the Eastern Badia schools. To achieve this, the cell unit and human body tissues were developed from the biology book for the ninth grade in light of the principles of visual learning. Applied. To measure the skill of reading pictures, an objective test was prepared in its final form of (25) items of a multiple-choice type. School year 2019/2020 AD. Where two groups were chosen randomly as an experimental group, and the number of its members reached 22 students and 26 students, they studied using the developed educational unit, and the other two divisions were considered as a control group, the number of whose members reached 19 students and 23 students, who were studied using the regular unit. The results of the study showed that there is a statistically significant difference in developing scientific image reading skills between the performances of the members of the two study groups in favor of the performance of the members of the experimental group. The researchers recommend the use of visual learning in science education in general and biology teaching in particular as one of the effective learning methods that work to achieve many goals of science education. And training teachers to use more effective strategies and models in meeting the needs of students so that they have an impact in developing the skills of reading scientific images and conducting more research and studies on the skills of reading scientific images in other regions and on other classes, and training teachers to use more effective strategies and models in meeting the needs of students so that they have an impact in developing the skills of reading scientific images and conducting more research and studies on the skills of reading scientific images in other regions and on other classes.